Effective metal shields of high voltage distribution cable lines - Popovic, Ljubivoje M. (Institute of Advanced Engineering and Science, 2023)
The presented methodology enables determining induced currents and voltages relevant to the correct estimation of security conditions required in operating and maintenance of the metal installations surrounding high-voltage distribution cable lines. It is based on the on-site measurements of currents appearing in two phase conductors of the considered cable line during a simulated ground fault in the supplied substation. Their values are utilized to compensate for the deficiency of all relevant but unknown data concerning the surrounding metal installations. It was done by introducing an equivalent cable shield substituting, from the standpoint of inductive influence, all surrounding metal installations. Here is shown that this equivalent shield can be determined in such a way that it becomes identical from the standpoint of its appearance to the actual cable line shield but with a changed value of its longitudinal resistance. When this value is determined for single-core cables belonging to a certain cable line it becomes possible to determine the actual reduction factor, inductive influence, and sequence impedance of the considered cable line by using a standard and well-known calculation procedure.